The effect of global energy price fluctuations on oil derivative prices and domestic prices in Jordan: GARCH model - Al-Damour, Saba Bassam; Adailah, Radi Mohammad; Al-Majali, Ahmad Abedalqader (Journal of Economic, Administrative and Legal Sciences, 2023)
The main objective of this study is to measure the extent to which global energy price fluctuations impact local oil derivative prices and the subsequent effect of local oil derivative price fluctuations on domestic prices. The study aims to contribute to finding solutions that mitigate the risks associated with energy price fluctuations and provide them to policymakers in Jordan. Given the lack of a clear understanding among policymakers and producers regarding the economic expectations of global energy prices and their impact on local prices, the study assumes a statistically significant relationship at a 5% level of significance between global energy prices, local energy prices (oil derivatives), and commodity and service prices. The methodology employed in the study involves estimating a GARCH model using monthly data for global energy prices, local energy prices, and the consumer price index for the period 2008-2022. The results of the study indicate that global oil prices (Brent) cause fluctuations in local oil derivative prices, while the reverse relationship does not hold. In other words, the relationship between oil prices and oil derivatives is unidirectional. The estimated GARCH model reveals that a 1% increase in Brent oil prices leads to a 0.21% increase in local oil derivative prices in Jordan, and a 1% increase in local oil derivative prices leads to a 0.23% increase in the consumer price index. The study recommends exploring mechanisms that can reduce the volatility of oil derivative prices in Jordan, as this would contribute to enhancing local price stability.